Estimating the summer residual flow based on sea surface temperature within a narrow strait - Juncheng Xie; Peng Bai; Xiaowei Xu; Lingling Xie; Mingming Li; Ying Gao (Frontiers in Marine Science)
Residual flow in straits manifests the interactions of multiple dynamic processes and serves as pivotal connectors between these processes, playing a crucial role in marine material-energy transport and ecosystem evolution. Current research predominantly relies on in-situ measurements and numerical modeling, yet both approaches incur high costs and struggle to obtain long-term residual current datasets, constraining our understanding of marine environments in straits and their adjacent basins. Addressing this gap, we developed an innovative algorithm to inversely calculate residual flow using satellite-derived sea surface temperature (SST) data, with a case study on the tide-dominated narrow Qiongzhou Strait in the northern South China Sea. Capitalizing on its distinctive summer SST pattern (eastern cooling vs. western warming) and prevailing westward residual current regime, we demonstrated that the thermal structure can be effectively characterized by a 1D balance equation incorporating temporal variation, horizontal advection, diffusion, and thermal forcing terms. Applying this framework to MODIS SST data (2003–2022), we reliably estimated summer residual flow velocities and fluxes over two decades. The analysis further revealed significant interannual variability in westward flow intensity, modulated by large-scale air-sea interactions: cyclonic wind anomalies over the northwestern South China Sea enhance westward currents, while anticyclonic anomalies induce weakening. This approach provides a cost-effective paradigm for monitoring long-term strait dynamics.